2021
DOI: 10.1101/2021.02.07.21251201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A prospective double-blinded non-selection trial of reproductive outcomes and chromosomal normalcy of newborns derived from putative low/moderate-degree mosaic IVF embryos

Abstract: Background Next generation sequencing (NGS) has increased detection sensitivity of intermediate chromosome copy number variations (CNV) consistent with chromosomal mosaicism. Recently, this methodology has found application in preimplantation genetic testing (PGT) of trophectoderm (TE) biopsies collected from IVF-generated human embryos. As a consequence, the detection rate of intermediate CNV states in IVF embryos has drastically increased, posing questions about the accuracy in identifying genuine mosaicism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The first prospective, nonselection randomized controlled trial has now reported that there are no differences in pregnancy and live birth outcomes from transfer of putative mosaic embryos up to 50% compared to euploid embryos. 35 There are multiple factors that can affect the detection of mosaicism in preimplantation embryos. A prime consideration is the extent to which a random sampling of 5-10 cells accurately reflects the genomic picture in the remainder of the embryo.…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The first prospective, nonselection randomized controlled trial has now reported that there are no differences in pregnancy and live birth outcomes from transfer of putative mosaic embryos up to 50% compared to euploid embryos. 35 There are multiple factors that can affect the detection of mosaicism in preimplantation embryos. A prime consideration is the extent to which a random sampling of 5-10 cells accurately reflects the genomic picture in the remainder of the embryo.…”
Section: Clinical Significancementioning
confidence: 99%
“…One major concern with mosaic embryo transfer studies is that the group receiving the putative mosaic embryos is enriched for patients where previous transfer with euploid embryos failed to implant. The first prospective, nonselection randomized controlled trial has now reported that there are no differences in pregnancy and live birth outcomes from transfer of putative mosaic embryos up to 50% compared to euploid embryos 35 …”
Section: Mosaicism In Human Preimplantation Embryosmentioning
confidence: 99%
“…In addition, karyomapping analysis demonstrated that 36% of embryos with chromosome copy numbers in the intermediate mosaic range were actually euploid (9). In addition, embryos with ''low-level'' mosaicism have been shown to possess equivalent reproductive potential to embryos designated as euploid (10,11). As shown in Table 1, several studies have reported successful outcomes after the transfer of ''mosaic" embryos, and, coincidently, with an overall success rate of 38%.…”
Section: Origins Of False Positive Mosaicismmentioning
confidence: 99%
“…An illustration of the impact of noise level on the accuracy of predicting euploidy (less noise) and error rate when predicting mosaicism (more noise) with simple copy number thresholds. ''putative'' mosaic embryos (10,33,42) or embryos with PGT-A profiles ''consistent with possible mosaicism'' (7). All clinical outcomes after the transfer of embryos designated as ''mosaic'' should be critically re-evaluated, with the idea that many of these embryos have been misclassified as mosaic and are actually uniformly euploid or uniformly aneuploid.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation